RBP differentiation contributes to selective transmissibility of OPT3 mRNAs. Issue 3 (2nd August 2021) - Lv, Xinmin; Sun, Yaqiang; Hao, Pengbo; Zhang, Cankui; Tian, Ji; Fu, Mengmeng; Xu, Zhen; Wang, Yi; Zhang, Xinzhong; Xu, Xuefeng; Wu, Ting; Han, Zhenhai
Abstract: Long-distance mobile mRNAs play key roles in gene regulatory networks that control plant development and stress tolerance. However, the mechanisms underlying species-specific delivery of mRNA still need to be elucidated. Here, the use of grafts involving highly heterozygous apple ( Malus ) genotypes allowed us to demonstrate that apple ( Malus domestica ) oligopeptide transporter3 ( MdOPT3 ) mRNA can be transported over a long distance, from the leaf to the root, to regulate iron uptake; however, the mRNA of Arabidopsis ( Arabidopsis thaliana) oligopeptide transporter 3 ( AtOPT3), the MdOPT3 homolog from A. thaliana, does not move from shoot to root. Reciprocal heterologous expression of the two types of mRNAs showed that the immobile AtOPT3 became mobile and moved from the shoot to the root in two woody species, Malus and Populus, while the mobile MdOPT3 became immobile in two herbaceous species, A. thaliana and tomato ( Solanum lycopersicum ). Furthermore, we demonstrated that the different transmissibility of OPT3 in A. thaliana and Malus might be caused by divergence in RNA-binding proteins between herbaceous and woody plants. This study provides insights into mechanisms underlying differences in mRNA mobility and validates the important physiological functions associated with this process. Abstract : The long-distance movement of OPT3 is selective between herbaceous and woody plants as shown using Malus and Arabidopsis thaliana plants.